Sikap Dan Pemilihan Bahasa Santriwati Di Pondok Pesantren Al-Furqon Driyorejo Gresik - Anisa Ramdhani; Maria Mintowati (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the language attitudes of female students toward Indonesian and Javanese, analyze language choice in formal and informal communication, and examine the relationship between language attitudes and language choice at Al-Furqon Islamic Boarding School, Driyorejo, Gresik. The study employed a descriptive mixed-method approach. Quantitative data were collected through questionnaires distributed to 78 female students selected using the Slovin formula from a population of 350 students, while qualitative data were obtained through Focus Group Discussions (FGD). Data were analyzed using descriptive quantitative and qualitative techniques, including frequency distribution, percentage analysis, and interpretation of discussion findings. The results indicate that the students demonstrate positive language attitudes toward Indonesian as the national and official language used in formal boarding school activities. However, Javanese remains the dominant language in daily communication due to social closeness, habitual use, cultural identity, and communication comfort. Language choice is influenced by communication context, interlocutors, and the linguistic norms applied within the boarding school environment. The findings reveal a relationship between language attitudes and language choice, indicating that positive language attitudes influence the tendency to use a particular language according to the communication context. This study contributes to sociolinguistic research by providing insights into language use dynamics in a multilingual Islamic boarding school environment.